Evaluating Carbon Farming Practices for Sustainable Soil Management in Citrus Cultivation - Nikolaou, Eirini; Christoforou, Michalakis; Dimitriadi, Stavroula; Efstathiou, Styliana; Eliades, Marinos; Hadjimitsis, Diofantos G.; Neophytou, Eleni; Papadavid, George; Stavrinides, Menelaos; Tzouvaras, Marios; Varvaris, Ioannis; Papoutsa, Christiana (My University, 2025)
Oranges (citrus) stand out as a fruit of global nutritional and consequently commercial importance, serving as an important export product for many countries. Their cultivation in Mediterranean climates requires careful management of soil and water resources, where maintaining fertile and healthy soils is vital for ensuring productivity and fruit quality. Carbon sequestration in soils of citrus orchards represents a significant opportunity for climate change mitigation. The carbon sequestration potential of citrus trees lies in their ability to remove CO2 from the atmosphere and store it in their biomass and soil. Depending on how the soil is managed and what practices are applied, the tree’s ability to sequester carbon is also affected. Studies reviewed in the context of the current mini-review, demonstrate that carbon sequestration agriculture such as cover cropping, reduced or no-tillage, pruning residue incorporation, and biochar / compost application significantly improve soil quality and can increase carbon sequestration. In addition, both biochar and compost, improve soil properties by increasing Cation Exchange Capacity (CEC) and balancing the pH, thereby enhancing nutrient availability for plants. These amendments aid in rehabilitating degraded soils, improve aeration and moisture retention, and support extensive root systems, which assist in carbon sequestration. Monitoring, Reporting and Verification frameworks are essential for enabling and incentivizing the application of carbon farming practices, and remote sensing technologies can provide valuable information for soil organic carbon (SOC) content monitoring over large areas. The current mini-review aims at discussing the potential of different practices for elevating SOC in citrus orchards and the potential applications of using remote sensing to monitor SOC levels in citrus orchards.
Keywords: Carbon farming; soil quality; carbon sequestration; citrus cultivation; sustainability; carbon storage